RANCANGAN SISTEM INFORMASI KONVERSI MATA KULIAH MAHASISWA PINDAHAN DAN LANJUTAN (STUDI KASUS DI STMIK LOMBOK) - Musyarrofah, Siti; Ashari, Maulana; fadli, sofiansyah (JISA(Jurnal Informatika dan Sains), 2019)
Lombok Institute of Information and Computer Management (STMIK) is one of the colleges in Central Lombok. In Higher Education there is a set of subjects given to participants in a period of education called the curriculum. Because the curriculum in each tertiary institution is different, a system that can equalize or convert courses is needed. Especially in supporting all lecture activities which in Higher Education must have a conversion system for equalizing subjects along with the number of effective semester credits takes up to two days, the head of study program is required to be able to produce or which is often referred to as a conversion term, both for advanced students and transfer students. The process of converting courses has not resulted in a decision that is a fast and appropriate decision for transfer student lectures. Based on the description above, the author intends to make a design entitled "The Design of Information Systems Conversion for Transfer and Advanced Students (Case Study of STMIK Lombok)".